HUBUNGAN MEKANISME KOPING DENGAN TINGKAT STRES PADA LANSIA PENSIUNAN DI RW. 04 TAMBAKBAYAN CATURTUNGGAL DEPOK SLEMAN YOGYAKARTA TAHUN 2014 - Firtson Alsuinfo Kamengbila; Patria Asda; Aris Budi Pratama (STIKES Wira Husada Yogyakarta, 2016)
ABSTRACTBackground: The elder is a natural process in becoming old. These days, someone will experience a physical and mental decrease, and also social step by step. This life condition will bring its own burden where someone will leave their daily job that has been done for a long time. It will be causing stress, especially to the people that will be retired. Retirement often considers as a unpleasant reality so before the time, some people will feel stressed because they cannot imagine what kind of life that they will faced after that. To deal with the stress on the elder pensioner, these retirements need a self-defense mechanism. There are two kinds of koping mechanism, task oriented reaction and ego oriented reaction. Objective: To know the coping mechanism with level of stress on the retirement elder at RW 04 Tambakbayan Caturtunggal Depok Sleman Yogyakarta.Method: This is a quantitative research with cross sectional design. The sample was taken by using total sampling, and the data were analyzed by using Spearman Rank. Result: Based on the result using Spearman Rank, it was found the probability value 0,000. Because of P<0,05 and that means Ho accepted and Ha was rejected so there’s signiﬁ cant relation between coping mechanism with the stress level on retirement elder.Conclusion: There’s relation between coping mechanisms with the stress level on retirement elder at RW 04 Tambakbayan Caturtunggal Depok Sleman Yogyakarta.